2023
DOI: 10.1002/cctc.202201410
|View full text |Cite
|
Sign up to set email alerts
|

Control in Advanced Biofuels Synthesis via Alcohol Upgrading: Catalyst Selectivity to n‐Butanol, sec‐Butanol or Isobutanol

Abstract: Ruthenium complexes with tetradentate PNNP donor ligands demonstrate a marked change in selectivity compared to analogous bis bidentate PN complexes in Guerbet catalysis, producing mixtures of n-butanol (17 %), sec-butanol (14 %) and ethyl acetate (66 %) rather than the usual 90 % + selectivity to n-butanol. Tridentate PNP ruthenium complexes such as [Ru-(H)(Cl)(CO)(Ph 2 PCH 2 CH 2 NHCH 2 CH 2 PPh 2 )] also produce sec-buta-nol and, in optimized conditions (120 °C, 10 mol% NaOEt base), achieve 71 % selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…selectivity, TOF) are targeted, this performance is similar to the best existing examples. 29–33,39,43…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…selectivity, TOF) are targeted, this performance is similar to the best existing examples. 29–33,39,43…”
Section: Resultsmentioning
confidence: 99%
“…24 The reaction pathway includes dehydrogenation of simple alcohol, base-catalyzed aldol condensation reaction and rehydrogenation of the aldol product. 25 Our group [26][27][28][29][30][31][32][33] and others [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] have been seeking new homogeneous catalysts for ethanol upgrading via Guerbet chemistry. Despite these recent advances, there is still significant scope for further catalyst development.…”
Section: Introductionmentioning
confidence: 99%
“…Wass and coworkers showed that trans ‐ Ru ‐ 13 and Ru‐14 complexes supported by small bite angle diphosphines and by mixed donor P−N ligands, respectively, are effective catalysts leading to the product with fair to good conversion and very high selectivity (Scheme 14). [49a,c] In 2017, trans ‐ Ru‐13 in combination with NaOH (200 mol %) was also applied to a mixture of ethanol and methanol containing the same amount of water present in the fermentation broth (85 %) [49b] . The reaction performed at 180 °C for 2 h led to isobutanol in 36 % yield and 78 % selectivity.…”
Section: Dehydrogenative Alcohol Activationmentioning
confidence: 99%
“…Herein, we demonstrate the catalytic transformation of ethanol to 2-butanol with pincer complexes Ru-MACHO ( Ru-1 ) and Ru-MACHO-BH ( Ru - 2 ), as well as the formation of low amounts of 2-butenes/butane (≤5%) under mild conditions (Figure , lower pathway) . Simply shifting to the analogous complex Ru - 5 , with the P -substituents changing to t -butyl groups, leads to the production of 1-butanol instead (Figure , upper pathway).…”
mentioning
confidence: 99%